Queer Reflections on Baron Wilhelm von Gloeden: A Creative Reconsideration of Pose, Gaze and Technique - Radić, Xavier (Auckland University of Technology, 2004)
This project and accompanying exegesis consider the evolution of the Gay, nude male analogue photograph, bringing to the fore a personalised reflection on the work of Baron Wilhelm von Gloeden. It contexualizes and investigates (from a queer perspective) issues of the pose and gaze, and revisits some of Von Gloeden’s constructions and technological concerns. These issues are then creatively synthesized into the production of a contemporary nude, male calendar. The photographs use self-identifying gay men as models. The artwork explores the potential of a range of increasingly anachronistic technologies [cyanotype, letter press and treatments of the analogue negative] to produce a print-based artefact that reflects upon notions of male grace, obscurification and the gaze.
Keywords: Male nude in art; Photography of the nude; Photography of men; Photography